2007
DOI: 10.1167/iovs.06-1485
|View full text |Cite
|
Sign up to set email alerts
|

Association between Heat Shock Protein 70/Hom Genetic Polymorphisms and Uveitis in Patients with Sarcoidosis

Abstract: PURPOSE. The predisposition to sarcoidosis, a systemic granulomatous disorder of unknown etiology, is genetically determined, and genetics appears also to drive the disease down distinct phenotypic pathways. This study was undertaken to test the hypothesis that sarcoidosis-related uveitis represents a genetically distinct disease subset, by investigating single nucleotide polymorphisms (SNPs) in the HSP-70/1 and HSP-70/ Hom genes. HSP70 molecules play a key role in the immune response by functioning both as ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 33 publications
0
25
1
1
Order By: Relevance
“…Further studies are needed to address the molecular mechanisms by which the HSP70 gene is involved in the development of SSNHL. The associations of the HSPA1L (HSP70-Hom) SNP rs2075800 with the predisposition to some autoimmune diseases has been documented previously [Jenkins et al, 2000;Bogunia-Kubik et al, 2006;Spagnolo et al, 2007]. The HSPA1L (HSP70-Hom) rs2075800 T allele is associated with rheumatoid arthritis [Jenkins et al, 2000], and the HSPA1L SNP rs2075800 C allele is associated with the susceptibility to sarcoidosis and Lofgren's syndrome [Bogunia-Kubik et al, 2006].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Further studies are needed to address the molecular mechanisms by which the HSP70 gene is involved in the development of SSNHL. The associations of the HSPA1L (HSP70-Hom) SNP rs2075800 with the predisposition to some autoimmune diseases has been documented previously [Jenkins et al, 2000;Bogunia-Kubik et al, 2006;Spagnolo et al, 2007]. The HSPA1L (HSP70-Hom) rs2075800 T allele is associated with rheumatoid arthritis [Jenkins et al, 2000], and the HSPA1L SNP rs2075800 C allele is associated with the susceptibility to sarcoidosis and Lofgren's syndrome [Bogunia-Kubik et al, 2006].…”
Section: Discussionmentioning
confidence: 98%
“…The HSPA1L (HSP70-Hom) rs2075800 T allele is associated with rheumatoid arthritis [Jenkins et al, 2000], and the HSPA1L SNP rs2075800 C allele is associated with the susceptibility to sarcoidosis and Lofgren's syndrome [Bogunia-Kubik et al, 2006]. A strong association between HSPA1L SNP rs2075800 and the increased risk of uveitis has been reported in patients with sarcoidosis, which suggests that the C allele of this SNP is a risk factor of sarcoidosis-related uveitis [Spagnolo et al, 2007]. Spagnolo et al [2007] postulated that the altered expression of HSPA1L influences the ability of the cell to withstand inflammation or alters the apoptotic threshold within the eye.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SNP1 of the HSPA1L gene is a non-synonymous variation; lysine is substituted for glutamate. Spagnolo et al [2007] reported a strong association between HSPA1L SNP rs2075800 and the increased risk of uveitis in patients with sarcoidosis, and suggested that the C allele of this SNP is a risk factor of sarcoidosis-related uveitis. They postulated that the altered expression of HSPA1L may influence the ability of the cell to withstand inflammation or alter the apoptotic threshold within the eye.…”
Section: Discussionmentioning
confidence: 99%